High hopes - Dubosarsky, Ursula, 1961- (Ringwood, Vic. : Penguin, 1990)
Julia arranges for her Argentinian born father to have English lessons, and struggles to cope with the consequences of her widowed father falling in love with the teacher.
"Puffin Books'.
For children.
For children
Keywords: Families -- Australia -- Juvenile fiction; Teachers -- Juvenile fiction